The Rise of the National Front and the De-demonization (dédiabolisation) Strategies - Mitrovic, Rados (Political Life, 2026)
The controversial political figure of Jean-Marie Le Pen significantly influenced the formation of the so-called “cordon sanitaire” by mainstream parties in France, which for many years prevented the National Front from becoming a significant actor in the formation of the executive government. Although the party achieved high electoral results in certain cycles, it did not have the opportunity to materialize these successes. For this reason, the main task of Marine Le Pen, who took over the party in 2011, was to, in a sense, “rebrand” the party, reform it, and “liberate” it from its “extremist” image. The first step was distancing the party from its founder, and later renaming it – the National Rally. This paper deals with this process of “de-demonization” initiated by Marine Le Pen, examining its causes and ultimate outcomes.